Droplet-based microfluidics in biomedical applications. (24th January 2022) - Amirifar, Leyla; Besanjideh, Mohsen; Nasiri, Rohollah; Shamloo, Amir; Nasrollahi, Fatemeh; de Barros, Natan Roberto; Davoodi, Elham; Erdem, Ahmet; Mahmoodi, Mahboobeh; Hosseini, Vahid; Montazerian, Hossein; Jahangiry, Jamileh; et al.
Abstract: Droplet-based microfluidic systems have been employed to manipulate discrete fluid volumes with immiscible phases. Creating the fluid droplets at microscale has led to a paradigm shift in mixing, sorting, encapsulation, sensing, and designing high throughput devices for biomedical applications. Droplet microfluidics has opened many opportunities in microparticle synthesis, molecular detection, diagnostics, drug delivery, and cell biology. In the present review, we first introduce standard methods for droplet generation (i.e. passive and active methods) and discuss the latest examples of emulsification and particle synthesis approaches enabled by microfluidic platforms. Then, the applications of droplet-based microfluidics in different biomedical applications are detailed. Finally, a general overview of the latest trends along with the perspectives and future potentials in the field are provided.